A TABU SEARCH APPROACH FOR PERMUTATION FLOW SHOP SCHEDULING - DODU, Cristina Elena; ANCĂU, Mircea (Studia Universitatis Babeș-Bolyai Informatica, 2020)
The adaptive distance between the neighbourhood’s makespans influences the local search to explore the non-investigated areas of the solutions space. A Tabu Search with the intensive concentric exploration over non-explored areas is proposed as an alternative solution to the simplest Tabu Search with the random shifting of two jobs indexes operation for Permutation Flow Shop Problem (PFSP) with the makespan minimization criteria.